Hypersexualized Monsters in ›Beowulf‹ Director’s Cut (USA 2007) and the Sharp Objects Constantly Threatening to Castrate Him - van Beek, Alan Lena (Mittelalter Digital, 2021)
This essay explores the 2007 cinematic adaptation of ›Beowulf‹, written by Neil Gaiman and Roger Avary. It will focus on narration, sexuality and virility in in the original poem and hypersexualized bodies in the movie. Gilded genitalia, absent genitalia and the sharp objects constantly threatening to castrate Beowulf are being analysed as a cultural text.